PERSPEKTIF HUKUM ISLAM TERHADAP IMPLEMENTASI PROGRAM DANA AMANAH PEMBERDAYAAN MASYARAKAT (DAPM) DI UPK (UNIT PENGELOLA KEGIATAN) BANGKIT MANDIRI ARJASA”. - Sasmita Nurfaradisa; Muhammad Jufri (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2022)
In the life of the community is a lot of things that we can take advantage of One of the most common things in society is the habit of people who need money to fulfill their lives and one of their ways is to borrow money. The habit has become a deep rooted tradition in the midst of social life including in Kedungdowo Village, Arjasa subdistrict, Situbondo district. Which money loan is allocated by the Activity Management Unit (UPK) Bangkit Mandiri Arjasa. So, the problem formulation was born such as : (1) What is the implementation of program DAPM (Dana Amanah Pemberdayaan Masyarakat) in Activity Management Unit (UPK) Bangkit Mandiri Arjasa? (2) How is the perspective of Islamic law on the implementation of program DAPM (Dana Amanah Pemberdayaan Masyarakat) in Activity Management Unit (UPK) Bangkit Mandiri Arjasa? To answer the problem formulation, this research uses qualitative analysis method. That’s research is explain object which related with problem research without related with variable research relationship. Method of collecting data which used researcher is observation method, interview method, and dokumentation method. Based on the results of this research, can be seen that implemntation of community empowerment intruction fund program (DAPM) in Activity Management Unit (UPK) Bangkit Mandiri Arjasa isn’t allowed in islam because it requires the practice of accounts payable (loan) in Activity Management Unit (UPK) Bangkit Mandiri Arjasa is not allowed because it require the addition of money back at the beginning of the contract.